The Pharmacodynamics Study of Insect Defensin DLP4 Against Toxigenic Staphylococcus hyicus ACCC 61734 in Vitro and Vivo - Ma, Xuanxuan; Yang, Na; Mao, Ruoyu; Hao, Ya; Yan, Xue; Teng, Da; Wang, Jianhua (Frontiers in Cellular and Infection Microbiology, 2021)
Staphylococcus hyicus (S. hyicus), as the main pathogen of exudative epidermitis (EE) in piglet, can cause a wide variety of diseases, ranging from bovine mastitis, chicken arthritis and even human sepsis, which has brought serious threats to animals and human. The potential threat of S. hyicus infection to both public and animal health has aroused great concern. The aim of our study was to explore the efficacy of insect defensin DLP4 against S. hyicus ACCC 61734 in vitro and in vivo. The in vitro efficacies of DLP4 against S. hyicus ACCC 61734 showed high antibacterial activity (0.92 μM), a long postantibiotic effect (9.54 h), a synergistic effect with ceftriaxone, penicillin and amoxicillin, a stable bacteriostatic effect, and intracellular bacteriostatic activity against S. hyicus ACCC 61734 in HaCaT cells. Besides, the antibacterial mechanism of DLP4 against S. hyicus ACCC 61734 was explored for the first time, which indicated that the antibacterial effect of DLP4 was related to its ability to destroy cell wall and generate membrane vesicles. The in vivo therapeutic effect of DLP4 was evaluated through mouse abscess model, and the results showed that DLP4 could effectively alleviate the mouse skin abscess by inhibiting bacterial proliferation and regulating cytokines. This study first demonstrated that DLP4 may be a promising therapeutic agent against S. hyicus ACCC 61734 infection.